Prevalence and predictors of malnutrition during adolescent pregnancy in southern Ethiopia: a community-based study - Belete Yimer; Awraris Wolde (BMC, 2022)
Abstract Background Adolescent pregnancy is a major public health problem with significant medical, nutritional, social and economic risk for mothers and their infants. The purpose of this study was to determine prevalence and predictors of malnutrition among pregnant adolescents in Kore district, southern Ethiopia. Methods Data were obtained from randomly selected consenting four hundred twenty five pregnant adolescents on March 2018 using interviewer-administered questionnaire and mid upper arm circumference (MUAC) measurement. A multivariable logistic regression analysis was used to identify the predictors of malnutrition in adolescent pregnancy. Results The study showed that 26.4% of study participants were malnourished (MUAC < 22 cm). Not owning livestock (AOR = 1.67, 95% CI = 1.26-2.19), unintended pregnancy (AOR = 1.36, 95% CI = 1.08-1.65), excess physical work in pregnancy (AOR = 1.29, 95% CI = 1.02-1.62) and being in the second (AOR = 1.70, 95% CI = 1.09-2.65) or third (AOR = 1.99, 95% CI = 1.29-3.07) pregnancy trimester were positively associated with malnutrition risk. Improved dietary intake in pregnancy (AOR = 0.46, 95% CI = 0.33-0.63) and support perceived by adolescents in pregnancy (AOR = 0.59, 95% CI = 0.43-0.82) were negatively associated with malnutrition risk. Conclusion More than one-quarter of the study population were malnourished. The information provides insight into the public health strategies to reduce malnutrition risk of the pregnant adolescents. Interventions aimed at improving socioeconomic status, dietary practice and physical work/activity through effective supports in pregnancy are recommended.